Label-free quantitative proteomic profiling reveals differential plasma protein expression in patients with obesity after treatment with liraglutide - Masood, Afshan; Benabdelkamel, Hicham; Joy, Salini Scaria; Alhossan, Abdulaziz; Alsuwayni, Bashayr; Abdeen, Ghalia; Aldhwayan, Madhawi; Alfadda, Nora A.; Miras, Alexander Dimitri; Alfadda, Assim A. (Frontiers in Molecular Biosciences, 2024)
Treatment and management of obesity is clinically challenging. The inclusion of GLP-1 receptor agonists (GLP1RA) in the medical management of obesity has proven to be efficacious. However, mechanisms underlying the molecular changes arising from GLP1RA treatment in patients with obesity remain to be elucidated. A single-center, prospective study was undertaken to evaluate the changes in the plasma proteins after liraglutide 3 mg therapy in twenty patients (M/F: 7/13) with obesity (mean BMI 40.65 ± 3.7 kg/m2). Anthropometric and laboratory parameters were measured, and blood samples were collected at two time points: baseline, before initiating treatment (pretreatment group, PT), and after three months of receiving the full dose liraglutide 3 mg (posttreatment group, PoT). An untargeted label-free LC MSMS mass spectrometric approach combined with bioinformatics and network pathway analysis was used to determine changes in the proteomic profiles. The mean age of the study participants was 36.0 ± 11.1 years. A statistically significant change was observed in weight, BMI and HbA1c levels between the PT and PoT groups (paired t-test, P < 0.001). A significant dysregulation was noted in the abundances of 151 proteins (31 up and 120 downregulated) between the two groups. The potential biomarkers were evaluated using receiver operating characteristic (ROC) curves. The top ten proteins (area under the curve (AUC) of 0.999 (95% CI)) were identified as potential biomarkers between PT and PoT groups and included Cystatin-B, major vault protein, and plastin3, which were upregulated, whereas multimerin-2, large ribosomal P2, and proline-rich acidic protein 1 were downregulated in the PoT group compared with the PT group. top network pathway centered around dysregulation of MAPK, AKT, and PKc signaling pathways and related to cell-to-cell signaling and interaction, cellular assembly and organization, cellular compromise and score of 46 with 25 focus proteins. Through label-free quantitative proteomic analysis, our study revealed significant dysregulation of plasma proteins after liraglutide treatment, resulting in decreased inflammation and decreased oxidative stress, along with altered carbohydrate and lipid metabolism. Understanding actions of liraglutide at a molecular and systemic levels provides a holistic look into how its action induces weight loss and exerts other beneficial metabolic effects.